The Hungária Ring Road of Budapest - Mariann Simon (Architektúra & Urbanizmus)
In 1872, the Metropolitan Public Works Council decided on three rings for the capital of Budapest: the inner ring (Small Boulevard), the outer ring (Great Boulevard) and the suburban ring. Completing the Great Boulevard – including the two bridges connecting the Pest side with Buda – took about 20 years. In contrast, the suburban ring road was fully opened only after more than 120 years. The long construction time allows us to show how ideas have changed concerning the function of a city ring.